The accuracy of pre-operative (P)-POSSUM scoring and cardiopulmonary exercise testing in predicting morbidity and mortality after pancreatic and liver surgery: A systematic review. (February 2021) - Dutton, J.; Zardab, M.; De Braal, V.J.F.; Hariharan, D.; MacDonald, N.; Hallworth, S.; Hutchins, R.; Bhattacharya, S.; Abraham, A.; Kocher, H.M.; Yip, V.S.
Abstract: Background: Cardiopulmonary exercise-testing (CPET) and the (Portsmouth) Physiological and Operative Severity Score for the enUmeration of Mortality and Morbidity ((P)-POSSUM) are used as pre-operative risk stratification and audit tools in general surgery, however, both have been demonstrated to have limitations in major hepatopancreatobiliary (HPB) surgery. Materials and methods: The aim of this review is to determine if CPET and (P)-POSSUM scoring systems accurately predict morbidity and mortality. Eligible articles were identified with an electronic database search. Analysis according to surgery type and tool used was performed. Results: Twenty-five studies were included in the final review. POSSUM predicted morbidity demonstrated weighted O/E ratios of 0.75(95%CI0.57–0.97) in hepatic surgery and 0.85(95%CI0.8–0.9) in pancreatic surgery. P-POSSUM predicted mortality in pancreatic surgery demonstrated an O/E ratio of 0.75(95%CI0.27–2.13) and 0.94(95%CI0.57–1.55) in hepatic surgery. In both pancreatic and hepatic surgery an anaerobic threshold(AT) of between 9 0.5–11.5 ml/kg/min was predictive of post-operative complications, and in pancreatic surgery ventilatory equivalence of carbon dioxide(˙VE/˙VCO2) was predictive of 30-day mortality. Conclusion: POSSUM demonstrates an overall lack of predictive fit for morbidity, whilst CPET variables provide some predictive power for post-operative outcomes. Development of a new HPB specific risk prediction tool would be beneficial; the combination of parameters from POSSUM and CPET, alongside HPB specific markers could overcome current limitations. Highlights: Current pre-operative scoring for pancreatic and liver surgery is inaccurate. In pancreatic and liver surgery anaerobic threshold scores were predictive of complications. In pancreatic surgery ventilatory equivalence of carbon dioxide was predictive of mortality. P-POSSUM is inaccurate for predicting mortality and morbidity in pancreatic surgery.